Anterior-to-Posterior Migration of a Lumbar Disc Sequestration: Surgical Remarks and Technical Notes about a Tailored Microsurgical Discectomy. (10th January 2017) - Frati, Alessandro; Pesce, Alessandro; Palmieri, Mauro; Vangelista, Tommaso; Caruso, Riccardo; Salvati, Maurizio; Raco, Antonino
Abstract : Extrusion of disc material within the spinal canal complicates up to 28.6% of lumbar disc herniations. Due to the anatomical "corridors" created by the anterior midline septum and lateral membranes, relocation occurs with an anterior and anterolateral axial topography. Posterior migration is an extremely rare condition and anterior-to-posterior circumferential migration is an even rarer condition. Its radiological feature can be enigmatic and since, in more than 50% of cases, clinical onset is a hyperacute cauda equina syndrome, it may imply a difficult surgical decision in emergency settings. Surgery is the gold standard but when dealing with such huge sequestrations, standard microdiscectomy must be properly modified in order to minimize the risk of surgical trauma or traction on the nerve roots.